Potential Risks and Benefits Associated With the Genetic Modification of Crops for Improved Nutritional Content in South Africa - Lungelo, Julius (International Journal of Food Sciences, 2024)
Purpose: The aim of the study was to examine potential risks and benefits associated with the genetic modification of crops for improved nutritional content in South Africa Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: The study revealed that the genetic modification of crops addresses global challenges related to malnutrition, food insecurity, and public health. By enhancing the levels of essential nutrients such as iron, zinc, vitamin A, and folate in crops, genetically modified biofortified varieties have the potential to improve the nutritional status and well-being of populations, particularly in resource-constrained settings. Moreover, the adoption of GM biofortified crops has been shown to increase agricultural productivity, reduce production costs, and enhance economic returns for farmers, contributing to rural development and poverty alleviation. However, the potential risks associated with the genetic modification of crops cannot be overlooked. Concerns about food safety, environmental impact, and socio-economic equity necessitate careful consideration and proactive risk management strategies. Unique Contribution to Theory, Practice and Policy: Risk Perception Theory & Social Construction of Technology may be used to anchor future studies on potential risks and benefits associated with the genetic modification of crops for improved nutritional content in South Africa. Engage stakeholders, including farmers, consumers, civil society organizations, and government agencies, in decision-making processes related to the development, regulation, and deployment of GM biofortified crops can foster transparency, trust, and inclusivity, leading to more socially acceptable and sustainable outcomes in practice. Develop science-based regulatory frameworks that balance the potential risks and benefits of GM biofortified crops, ensuring safety, environmental sustainability, and public health protection.